2011
DOI: 10.4269/ajtmh.2011.10-0314
|View full text |Cite
|
Sign up to set email alerts
|

Using Geographic Information System-based Ecologic Niche Models to Forecast the Risk of Hantavirus Infection in Shandong Province, China

Abstract: Abstract. Hemorrhagic fever with renal syndrome (HFRS) is an important public health problem in Shandong Province, China. In this study, we combined ecologic niche modeling with geographic information systems (GIS) and remote sensing techniques to identify the risk factors and affected areas of hantavirus infections in rodent hosts. Land cover and elevation were found to be closely associated with the presence of hantavirus-infected rodent hosts. The averaged area under the receiver operating characteristic cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
(48 reference statements)
1
31
0
Order By: Relevance
“…According to the model results, predicted risks were divided into three levels: low (< 0.15), moderate (0.15-0.30), and high (> 0.30), and the mean relative risks of HV infection of rodents in study area. 13 Annual prediction maps showed high-risk areas always focused on the southwest of the study area (Hengyang city), and sporadically scattered in Changsha city, Shaodong County, and Zhuzhou city; however, low-and moderate-risk of infections always occurred in northwest and east region, north and middle of the study area, respectively. In 2010, high infection risk areas decreased and low infection risk areas appeared in southwest (Figure 3).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…According to the model results, predicted risks were divided into three levels: low (< 0.15), moderate (0.15-0.30), and high (> 0.30), and the mean relative risks of HV infection of rodents in study area. 13 Annual prediction maps showed high-risk areas always focused on the southwest of the study area (Hengyang city), and sporadically scattered in Changsha city, Shaodong County, and Zhuzhou city; however, low-and moderate-risk of infections always occurred in northwest and east region, north and middle of the study area, respectively. In 2010, high infection risk areas decreased and low infection risk areas appeared in southwest (Figure 3).…”
Section: Resultsmentioning
confidence: 91%
“…15,23,28 The appropriate precipitation leads to increased rodent food resources, affects the transmission of HFRS by influencing the living conditions and food supplies of rodents and the transmission between rodents and from rodents to humans; temperature affects the population of rodents by influencing the pregnancy numbers, litter size, birthrates, and survival rates, and appropriate temperatures were correlated to increased survival and recruitment, which lead to greater rodent population densities; the infectivity of HV is also influenced by temperature and precipitation. 11,13,15,29 But the higher the temperature, the shorter the survival of the HV outside the host. However, our results showed that TVDI and elevation were the main risk factors, and therefore temperature, precipitation, and NDVI were not included in the final logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large variations in altitude and rainfall result in a mosaic of vegetation types, including hills covered by extensive grasslands, narrow gallery forests, and rocky areas dominated by cactus [23]. Given this combination of floral characteristics and edaphic and pedological features, this unique ecosystem is very similar to the savanna of the Cerrado biome.…”
Section: Does Land Cover Influence the Spatial Distribution Of Reservmentioning
confidence: 99%
“…Glass et al [15][16][17] and Boone et al [18,19] used remote sensing images to identify environments associated with a risk of hantaviral disease in humans caused by Sin Nombre virus. Wei et al [20] combined ecologic niche modeling with remote sensing techniques to identify the risk factors for hantavirus infections in rodent hosts. Zhang et al [10] and Goodin et al [21] examined the relationship between natural infection rates for hantavirus in rodents and land cover classes.…”
Section: Introductionmentioning
confidence: 99%